Compartmentalisation and groundwater–surface water interactions in a prospective shale gas basin: Assessment using variance analysis and multivariate statistics on water quality data. Issue 15 (3rd June 2020) - Wilson, Miles P.; Worrall, Fred; Clancy, Sarah A.; Ottley, Chris J.; Hart, Alwyn; Davies, Richard J.
Abstract: An environmental concern with hydraulic fracturing for shale gas is the risk of groundwater and surface water contamination. Assessing this risk partly involves the identification and understanding of groundwater–surface water interactions because potentially contaminating fluids could move from one water body to the other along hydraulic pathways. In this study, we use water quality data from a prospective shale gas basin to determine: if surface water sampling could identify groundwater compartmentalisation by low‐permeability faults; and if surface waters interact with groundwater in underlying bedrock formations, thereby indicating hydraulic pathways. Variance analysis showed that bedrock geology was a significant factor influencing surface water quality, indicating regional‐scale groundwater–surface water interactions despite the presence of an overlying region‐wide layer of superficial deposits averaging 30–40 m thickness. We propose that surface waters interact with a weathered bedrock layer through the complex distribution of glaciofluvial sands and gravels. Principal component analysis showed that surface water compositions were constrained within groundwater end‐member compositions. Surface water quality data showed no relationship with groundwater compartmentalisation known to be caused by a major basin fault. Therefore, there was no chemical evidence to suggest that deeper groundwater in this particular area of the prospective basin was reaching the surface in response to compartmentalisation. Consequently, in this case compartmentalisation does not appear to increase the risk of fracking‐related contaminants reaching surface waters, although this may differ under different hydrogeological scenarios. Abstract : How vulnerable are surface waters to contamination from deep groundwater carrying fracking‐related fluids? Statistical analyses of newly collected surface water quality data and existing groundwater quality data indicate regional‐scale shallow groundwater–surface water interactions. However, no chemical signature of groundwater compartmentalisation by a low‐permeability fault was observed, suggesting deeper groundwater was not reaching the surface in response to compartmentalisation flow effects.